Comparison of treatment outcomes of stable and unstable developmental dysplasia of the hip with the Tübingen splint - Chaibi, Emmelie; Saugy, Claire-Anne; Samara, Eleftheria; Zambelli, Pierre-Yves; Merckaert, Sophie Rosa (Frontiers in Pediatrics, 2022)
Background The Tübingen splint was initially developed for the treatment of stable developmental hip dysplasia (DDH). Later on, some authors expanded its include for the treatment of unstable DDH, but there remain some controversies in the literature. This study aims to compare the outcome between stable and unstable DDH treated with a Tübingen splint. Methods Epidemiological data and ultrasonographic data of all infants diagnosed with DDH and initially treated with a Tübingen splint at our institution between May 2017 and February 2020 were assessed retrospectively. We divided the population into stable and unstable hips using the Graf classification. Age at treatment initiation, duration of treatment, complications, and radiological outcome between 12 and 24 months were investigated. Results We included a total of 45 patients (57 hips) affected by DDH treated with the Tübingen splint. Treatment has been successful in 93% of stable hips and only 40% of unstable hips. Radiological outcome at 1-year follow-up significantly correlated with initial Graf classification (p < 0.001). Conclusion The Tübingen splint is a safe and effective treatment for stable hips, nevertheless, for unstable hips, closed reduction, and spica cast remains the gold standard.